Christendom at the crossroads : the medieval era - Sheppard, James (Louisville : Kentucky : Westminster John Knox Press, 2005)
"In Christendom at the Crossroads, J.A. Sheppard explores the development of Christian theology in the medieval period. Expertly leading readers through the major theological controversies and issues of the era, Sheppard highlights why those particular questions were so important for Christian believers at that time. He uses the Apostles' Creed as the background to show how medieval theology developed, the ways that crucial issues were debated, and the effects those debates had on the church and Christian belief."--Jacket.
At the crossroads -- I believe -- In God the Father -- And in Jesus Christ -- Born of the Virgin Mary -- To judge the living and the dead -- In the Holy Spirit -- The road to the Reformation.
Includes bibliographical references (pages 155-159) and indexes.
Keywords: Church history -- Middle Ages, 600-1500.